Antiplasmodial activity of Mezoneuron benthamianum leaves and identification of its active constituents. (5th May 2017) - Jansen, Olivia; Tchinda, Alembert T.; Loua, Jean; Esters, Virginie; Cieckiewicz, Ewa; Ledoux, Allison; Toukam, Paul D.; Angenot, Luc; Tits, Monique; Balde, Aliou M.; Frédérich, Michel
Abstract: Ethnopharmacological relevance: Decoctions of the leaves of M. benthamianum Baill. are used by traditional healers in Guinea to treat malaria and this use was validated by a preliminary clinical assay. Aim of the study: To evaluate the in vitro antiplasmodial activity and to identify active compounds from extracts of M. benthamianum leaves. Material and methods: Antiplasmodial activity of extracts, fractions and pure compounds was evaluated in vitro against a chloroquine-sensitive strain of Plasmodium falciparum (3D7) using the measurement of the plasmodial lactate dehydrogenase activity. Selectivity of extracts and purified compounds for Plasmodium parasites was evaluated by using WST-1 test on HeLa human cells. Compounds were isolated using normal phase silica gel column chromatography and prepHPLC and their structures elucidated using extensive spectroscopic analysis. Results: Hydroethanolic extracts (70% v/v) of M. benthamianum leaves showed a moderate in vitro activity against P. falciparum 3D7, with IC50 in the range 22.5 – 32.6 µg/mL, depending on the batch; while a dark precipitate formed during ethanol evaporation showed higher activity (IC50 =6.5 µg/mL). The fractionation was performed on this most active fraction and was followed by in vitro antiplasmodial assay. Active compounds (5, 7, 8) belong to several phytochemical classes, contributing together to the global antiplasmodial activity of the hydroethanolic extract against P. falciparum parasite. This study finally allowed the isolation of three diterpenes including two new compounds named Mezobenthamic acids A (1) and B (2) and neocaesalpin H (3), as well as quercetin (4), kaempferol (7), resveratrol (6), gallic acid (9) and its ethylester (5), β-sitosterol glucoside (10) and 13b-hydroxy-pheophorbide a (8). Conclusion: This study gives some concrete evidence to support the ethnopharmacological use of Mezoneuron benthamianum leaves extract in the management of malaria. The active compounds can be further studied for their antiplasmodial potential, as well as their suitability to be used as quality markers for the standardization of this herbal drug from the Guinean traditional pharmacopeia. Graphical abstract: